Conducting Rapid Response Phone Surveys to Fill Data Gaps - Delius, Antonia (World Bank, Washington, DC, 2020)
To respond effectively to crises, policy makers need reliable, timely evidence on its negative effects and transmission channels. Despite limitations compared to face-to-face surveys, rapid response phone surveys (RRPS) are a cost-effective, flexible method to quickly fill data gaps. This note gives an overview of main considerations when setting up a RRPS. It also illustrates how surveyors have used this tool to inform design of interventions during Ebola and famine crises. The World Bank is currently using RRPSs to track the impact of Coronavirus 2019 (COVID-19) in more than 100 countries.